Efficiency of Rapidly Ageing Electronic Systems - Balaišis, P.; Eidukas, D.; Besakirskas, A.; Tervydis, P. (Elektronika ir Elektrotechnika, 2004)
In this paper the conception of electronic systems (ES) dynamics is presented. The class of rapidly ageing electronic systems ismarked out. It is shown, that efficiency and durability of these systems are determined by peculiarities of their devices and processes. Itis recommended to use unstationary, statistical (dynamic) conceptions of ES efficiency. The conception of dynamic efficiency isspecified.The method, how to evaluate efficiency and durability of ES, which are performing the same tasks, is presented.The evaluation model of durability for ES, performing changeable and random tasks, considering dynamics of system’s functionalpotentiality, is made. Proposed methods could be used even when indefectibility of ES is very big. Ill.5, bibl.3 (in Lithuanian;summaries in Lithuanian, Russian, English).